2017
DOI: 10.1007/s10548-017-0583-x
|View full text |Cite|
|
Sign up to set email alerts
|

The Callosal Relay Model of Interhemispheric Communication: New Evidence from Effective Connectivity Analysis

Abstract: Interhemispheric auditory connectivity via the corpus callosum has been demonstrated to be important for normal speech processing. According to the callosal relay model, directed information flow from the right to the left auditory cortex has been suggested, but this has not yet been proven. For this purpose, 33 healthy participants were investigated with 64-channel EEG while performing the dichotic listening task in which two different consonant–vowel syllables were presented simultaneously to the left (LE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 59 publications
2
20
0
2
Order By: Relevance
“…This finding indicates that an increased gamma-band synchrony goes along with more LE reports and also leads to a reduction of the typical left-lateralization of language. This is in accordance with two prior EEG studies, showing gamma-band oscillations and their synchronization are crucially involved in interhemispheric information transfer during conscious perception of LE syllables 1,21 . It is suggested that synchronized gamma-band activity constitute a fundamental brain mechanism that subserves the cortical computation underlying several cognitive functions 8 , such as auditory perception 58 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding indicates that an increased gamma-band synchrony goes along with more LE reports and also leads to a reduction of the typical left-lateralization of language. This is in accordance with two prior EEG studies, showing gamma-band oscillations and their synchronization are crucially involved in interhemispheric information transfer during conscious perception of LE syllables 1,21 . It is suggested that synchronized gamma-band activity constitute a fundamental brain mechanism that subserves the cortical computation underlying several cognitive functions 8 , such as auditory perception 58 .…”
Section: Discussionsupporting
confidence: 93%
“…The dichotic listening task used was the same as in our previous studies 1,15,21 . In brief, six different consonant-vocal syllables (/ba/, /da/, /ka/, /ga/, /pa/, /ta/) were paired and presented simultaneously: one syllable to each ear, resulting in 12 different combinations as only syllables with the same voice-onset time were combined 28 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Auditory connectivity via the corpus callosum has been reported to be responsible for the interplay of right and left speech-relevant brain regions [25]. It appears that there is a significantly increased effective connectivity in the gamma band from the right to the left secondary auditory cortex during conscious perception of left ear stimuli [25]. However, it remains unknown in which direction the interhemispheric communication is realized.…”
Section: Discussionmentioning
confidence: 99%